PENGARUH PENYULUHAN TERHADAP PETERNAK BABI DI KECAMATAN KAWANGKOAN - Rompas, Alma; Sajow, A A; Lombogia, S O.B; Warouw, Z M (Universitas Sam Ratulangi, 2020)
THE EXTENSION EFFECT ONÂ PIG FARMERS IN KAWANGKOAN DISTRICT. This research was conducted in Kawangkoan District in March 2020. This study aimed to determine the effect of extension on pig farmers in Kawangkoan District. This research was conducted by a survey method using a questionnaire. Sample was determined by Purposive toward 40 pig farmers. Analysis of the data used in this study was the Chi-Square analysis. The variable of extension, knowledge, attitudes and skills of pig farmers was measured using an ordinal scale. Then by scoring respondents' answers or statements given, several categories of the three variables were obtained. The categorical knowledge variable was increased knowledge, quite increasing and not increasing. The results of the study using Chi-Square Analysis showed that counseling had an influence on the knowledge, attitudes and skills of pig farmers.